Spilanthes acmella extract alleviates cisplatin-induced nephrotoxicity and DNA damage in human embryonic kidney cells - Manju, L; Ambili, S; Vishnu, S L; Radhika, A; Rajesh, R (Plant Science Today, 2025)
Kidney dysfunction has a devastating effect on health and quality of life, as it is one of the vital organs responsible for maintaining body homeostasis. Chemotherapeutic agents, especially anticancer medications, induce significant toxicity, resulting in renal dysfunction and irreversible kidney damage. This has led to a renewed focus on finding safer, more effective alternatives, such as pharmaceuticals derived from natural sources. The present study investigates the protective effects of ethyl acetate extract of Spilanthes acmella (EASA) against cisplatin-induced nephrotoxicity in human embryonic kidney (HEK293) cells. Preliminary phytochemical screening revealed Alkaloids and phenols as the predominant constituents. A neutral red uptake assay determined the non-toxic concentration of S. acmella and the combinatorial treatment with EASA restored cell viability to 72 %, compared to 47 % in cisplatin treated cells. The antioxidant enzymes SOD and catalase were shown to be diminished by cisplatin, indicating oxidative damage, accompanied by an increase in lipid peroxidation products. EASA significantly elevated enzyme levels and reduced membrane peroxides. Reactive oxygen species production was shown to be reduced in groups co-treated with EASA, as assessed by DCFDA fluorimetry studies. The comet assay also showed a reduction in cisplatin-induced DNA damage following EASA co-treatment. These findings demonstrate that EASA may mitigate the oxidative stress generated by cisplatin, thereby preventing oxidative renal injury.